Extensão cultural e incentivo à leitura da Biblioteca Pública do Espírito Santo Levy Curcio da Rocha (1973-2008): programa Carro-Biblioteca e o Biblioteca Móvel - Barcellos, Marcileia Seibert de (2014)
The State Public Library of the Holy Spirit (BPES) was created in 1855. She is considered one of the oldest public libraries in Brazil and, since its founding, was surrounded by difficulties in functioning. This research focuses on the activity of cultural extension and encouragement of reading developed by BPES Levy Cúrcio da Rocha, through projects Car Library and Mobile Library from 1973 to 2008 shows that these projects are activities whose elements are enablers of questions, perceptions, conceptions, attitudes and diversity of reading. Explains that the focus of the work was guided by the cultural role of the public library, where reflections as to the various ways of understanding how culture is characterized by the social life of a people or nation, and even as she derives from this common set were identified concerns inherent to their sometimes divergent social realities. It also shows a brief history of car-library programs at the international and national scene and how a library can engage in a harmonious way and in harmony through its function as a cultural extension, serving the needs and interests of a community which is fixed. Shows the history of Library project car since its creation in 1973, covering its features, its main objectives and the results obtained by collecting data on primary sources and direct research through semi-structured interviews with their creators. He also reports that the proposed period, this cultural extension service through the Library car was off by a few years, due to factors inherent to the will of BPES, but resurfaced in 2008, via the Mobile Library, with the goal of continuing to improve and democratize the reading habit (through information) in underserved and remote communities of socioeconomic information of any nature.